أثر الأجل في عقد البيع عند المالكية وتطبيقاته السلم وابتداء الدين بالدين أنموذجا - بالقاسمي; جهاد (University of Eloued جامعة الوادي, 2024)
"هذا البحث الموسوم بـ ""أثر الأجل في عقد البيع عند المالكية وتطبيقاته -السلم وابتداء الدين بالدين أنموذجاً-، كان الإشكال الرئيس فيه: حول مدى تأثير الأجل في بيع السلم وابتداء الدين بالدين عند المالكية وتخريجه على التطبيقات المعاصرة، وقد حاولت الإجابة عنه في ثلاثة مباحث: في المبحث الأول تطرقت إلى ماهية الأجل وعقد البيع عند المالكية من حيث التعريف والأنواع والمشروعية والحكمة منها، ثم بيّنت أثر الأجل في عقد البيع عندهم من خلال مسألتي: تراخي الإيجاب عن القبول، والتمييز بين الأجل المعلوم والمجهول. وفي المبحث الثاني عنيت بدراسة عقد السلم عند المالكية من حيث تعريفه وحكمه وحكمته وتحديد شروطه، ثم وضحت أثر الأجل في السلم عندهم من خلال عدة مسائل أهمها: تأخير رأس مال السلم، ومدة عقد السلم، وحلول الأجل وتعذر التسليم، ثم ختمت المبحث بمعالجة مسائل معاصرة أهمها: السلم الموازي، وعقود التوريد، والسلم بسعر السوق؛ تخريجا لها على مذهب المالكية في السلم الذي تم تقريره. وعلى النسق نفسه كانت معالجة المبحث الثالث في بيان ماهية ابتداء الدين بالدين، وتخريج تطبيقاته المعاصرة على مذهب المالكية. وتوصلت الدراسة إلى جملة من النتائج ولعل أهمها أن أثر الأجل في صحة عقد البيع من عدمه يتعلق بتقدير اليسير من الفاحش في الأجل، ومرده إلى العرف الذي يتغير بتغير الزمان والمكان، وبهذا تظهر مرونة المذهب المالكي في بحث المعاملات المالية المعاصرة.""This research was entitled as “The effect of the term on the sale contract according to the Malikis and its applications – “Bai us Salam” ; as transliterated from Arabic (which is an Islamic contract in which full payment is made in advance for specific goods to be delivered at a future date.) and the beginning of debt with debt as an example -, the main problem in it was: about the extent of the effect of the term on Bai us Salam and the beginning of debt with debt according to the Malikism and its graduation on contemporary applications which I tried to answer in three sections: In the first section, I addressed the nature of the term and the contract of sale according to the Malikism in terms of definition, legal types, and its purpose. Then I explained the effect of the term in the contract of sale according to them through two issues: the laxity of the offer from acceptance, and the distinction between the known and unknown term. In the second section, we shed light on the contract of Bai us Salam in the light of Malikism in terms of its definition, Its legitimacy, purpose, and its conditions. Then, I explained the term in Bai us Salam according to Malikism point of view through several issues. The most important of which are: delaying the capital, the duration of the Bai us Salam contract, successful solutions, and the impossibility of exercising. Then I concluded the section by addressing contemporary issues, the most important of which are: Parallel Bai us Salam, supply contracts, Bai us Salam market price; according to Malikism in Bai us Salam was decided. In the same vein, the third topic was dealt with in explaining the nature of the beginning of debt with debt according to its contemporary applications to the Malikism doctrine. The study reached a number of results, perhaps the most important of which is that the effect of the term on the validity and invalidity of the sales contract is related to the estimation of what is excessive in the term, and is due to custom that changes with time and place. Thus, the flexibility of Malikism school of thought appears in the study of contemporary financial transactions.
Keywords: الأجل; المذهب المالكي; البيع; السلم; ابتداء الدين بالدين.; Malikism; sale; Bai us Salam; beginning debt with debt.